Early response by MR imaging and ultrasound as predictor of pathologic complete response to 12‐week neoadjuvant therapy for different early breast cancer subtypes: Combined analysis from the WSG ADAPT subtrials. Issue 10 (11th February 2021) - Graeser, Monika; Schrading, Simone; Gluz, Oleg; Strobel, Kevin; Würstlein, Rachel; Kümmel, Sherko; Schumacher, Claudia; Grischke, Eva‐Maria; Forstbauer, Helmut; Braun, Michael; Christgen, Matthias; Adams, Jascha; et al.
Abstract: We evaluated the role of early response after 3 weeks of neoadjuvant treatment (NAT) assessed by ultrasound (US), magnetic resonance imaging (MRI) and Ki‐67 dynamics for prediction of pathologic complete response (pCR) in different early breast cancer subtypes. Patients with HR+/HER2+, HR−/HER2− and HR−/HER2+ tumors enrolled into three neoadjuvant WSG ADAPT subtrials underwent US, MRI and Ki‐67 assessment at diagnosis and after 3 weeks of NAT. Early response was defined as complete or partial response (US, MRI) and ≥30% proliferation decrease or <500 invasive tumor cells (Ki‐67). Predictive values and area under the receiver operating characteristic (AUC) curves for prediction of pCR (ypT0/is ypN0) after 12‐week NAT were calculated. Two hundred twenty‐six had MRI and 401 US; 107 underwent both MRI and US. All three methods yielded a similar AUC in HR+/HER2+ (0.66‐0.67) and HR−/HER2− tumors (0.53‐0.63), while MRI and Ki‐67 performed better than US in HR−/HER2+ tumors (0.83 and 0.79 vs 0.56). Adding MRI+/‐Ki‐67 increased AUC of US in HR−/HER2+ tumors to 0.64 to 0.75. MRI and Ki‐67 demonstrated highest sensitivity in HR−/HER2− (0.8‐1) and HR−/HER2+ tumors (1, both). Negative predictive value was similar for all methods in HR+/HER2+ (0.71‐0.74) and HR−/HER2− tumors (0.85‐1), while it was higher for MRI and Ki‐67 compared to US in HR−/HER2+ subtype (1 vs 0.5). Early response assessed by US, MRI and Ki‐67 is a strong predictor for pCR after 12‐week NAT. Strength of pCR prediction varies according to tumor subtype. Adding MRI+/‐Ki‐67 to US did not improve pCR prediction in majority of our patients. Abstract : What's new? In breast cancer, a pathologic complete response (pCR) after neoadjuvant therapy (NAT) can predict long‐term outcome. However, rates of pCR differ according to EBC subtype. So what is the most useful approach to determine early response? In this prospective study, the authors compared MRI, ultrasound, and Ki‐67 status after three weeks of NAT. They found that MRI and Ki‐67 had higher sensitivity than ultrasound in HR‐/HER2+ and HR‐/HER2‐ tumors, while all three methods were similar for HR+/HER2+ tumors. These findings could guide identification of candidates for therapy de‐escalation or escalation.